2023
DOI: 10.19127/mbsjohs.1243023
|View full text |Cite
|
Sign up to set email alerts
|

The Difficulties Experienced by Nurses Working in A Tertiary Hospital in Turkey while Providing Health Care to Immigrant and Refugee Patients and Intercultural Sensitivity

Abstract: Objective: This research was carried out to evaluate the difficulties experienced by nurses during the delivery of health care to immigrant and refugee patients and their intercultural sensitivity. Methods: The descriptive-cross-sectional study was conducted with 132 nurses. In the study, "socio-demographic questions, questions about the difficulties experienced while caring for immigrant/refugee patients" and "Intercultural Sensitivity Scale (ISS)" were applied. Mean ± standard deviation, frequency, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Health services should regularly follow up on refugee children with chronic diseases. In the literature, it is stated that refugees experience some problems, such as not knowing their rights in accessing health services, having limited information about the language of the country they reside, having limited information about the general health system, and not being able to receive services following transcultural care principles (Beser & Tekkes Kerman, 2017;Derince, 2019;Ozdemir & Kiymaz, 2023). The fact that the cultures of the refugees are not adequately recognized by the health care professionals in the country they migrate to may negatively affect the provision of health care services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health services should regularly follow up on refugee children with chronic diseases. In the literature, it is stated that refugees experience some problems, such as not knowing their rights in accessing health services, having limited information about the language of the country they reside, having limited information about the general health system, and not being able to receive services following transcultural care principles (Beser & Tekkes Kerman, 2017;Derince, 2019;Ozdemir & Kiymaz, 2023). The fact that the cultures of the refugees are not adequately recognized by the health care professionals in the country they migrate to may negatively affect the provision of health care services.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the cultures of the refugees are not adequately recognized by the health care professionals in the country they migrate to may negatively affect the provision of health care services. Ozdemir and Kiymaz (2023) found that nurses with low transcultural sensitivity have difficulties while caring for refugee patients. Nurses' cultural sensitivity levels were found to be moderate in a study conducted on the southeastern border of Turkey, and it was stated that for effective health care delivery, health professionals should be trained in intercultural care and patient care plans should be adapted to take into account different cultural experiences (Uzun & Sevinc, 2015).…”
Section: Discussionmentioning
confidence: 99%